2020
DOI: 10.3390/f11050592
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships between Phlebiopsis gigantea and Selected Basidiomycota Species Inferred from Partial DNA Sequence of Elongation Factor 1-Alpha Gene

Abstract: Phlebiopsis gigantea (Fr.) Jülich has been successfully used as a biological control fungus for Heterobasidion annosum (Fr.) Bref., an important pathogen of pine and spruce trees. The P. gigantea species has been known for many years, but our understanding of the relationship between various isolates of this fungus has been substantially improved through the application of DNA sequence comparisons. In this study, relationships between P. gigantea and selected Basidiomycota species was determined, based on elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…In Clade A, a subclade A1 included two sequences from the US East coast (SCNC and MWV24089A) and one from the UK (GenBank: KU886025). We note, though, that sequence KU886024 from Poland fell in the Clade B, and the same was observed for all other sequences from the UK, that, although unavailable in GenBank, are reported in Wit et al [76], questioning the actual phylogenetic positioning or validity of the UK sequence KU886025. The phylogenetic analysis of the TEF1-α region identified two main genetic intraspecific A and B lineages, with average within-group distances of 0.02% and 0.11%, respectively.…”
Section: Translation Elongation Factor 1-alpha (Tef1-α)supporting
confidence: 71%
“…In Clade A, a subclade A1 included two sequences from the US East coast (SCNC and MWV24089A) and one from the UK (GenBank: KU886025). We note, though, that sequence KU886024 from Poland fell in the Clade B, and the same was observed for all other sequences from the UK, that, although unavailable in GenBank, are reported in Wit et al [76], questioning the actual phylogenetic positioning or validity of the UK sequence KU886025. The phylogenetic analysis of the TEF1-α region identified two main genetic intraspecific A and B lineages, with average within-group distances of 0.02% and 0.11%, respectively.…”
Section: Translation Elongation Factor 1-alpha (Tef1-α)supporting
confidence: 71%
“…Bref. Wit et al [29] utilized elongation factor 1-alpha (EF1α) partial DNA sequencing and in silico data to infer the relationships between representative isolates of P. gigantea and selected Basidiomycota species. The results obtained indicated that the EF1α region is a valid marker for selecting the most competitive isolates of P. gigantea to be possibly employed for limiting damage by forest tree root pathogens.…”
mentioning
confidence: 99%